1997
DOI: 10.3109/13651509709024707
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, phenomenology and comorbidity of body dysmorphic disorder (dysmorphophobia) in a clinical population

Abstract: Dysmorphophobia (body dysmorphic disorder), defined as a preoccupation with an imaginary or minimal defect in appearance, has been known for more than a century but has received relatively little empirical study. The authors investigated the demographics, phenomenology, course, associated psychopathology and family history in a series of 58 patients (34 men and 24 women) with the disorder. The patients were assessed with the Hopkins Symptom Checklist and two specially constructed instruments developed by the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
25
0
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(36 citation statements)
references
References 22 publications
9
25
0
1
Order By: Relevance
“…This finding is consistent with studies of out-patients ascertained for BDD, in which 45-70% reported a history of suicidal ideation attributed primarily to BDD [39,40], and 16% (of 100 subjects) attributed at least one suicide attempt primarily to BDD [40]. A limitation of the present study is that we did not obtain suicidality data in patients without BDD and thus cannot compare suicidality in patients with and without BDD.…”
Section: Discussionsupporting
confidence: 89%
“…This finding is consistent with studies of out-patients ascertained for BDD, in which 45-70% reported a history of suicidal ideation attributed primarily to BDD [39,40], and 16% (of 100 subjects) attributed at least one suicide attempt primarily to BDD [40]. A limitation of the present study is that we did not obtain suicidality data in patients without BDD and thus cannot compare suicidality in patients with and without BDD.…”
Section: Discussionsupporting
confidence: 89%
“…Our finding in the present study that BDD subjects had above average scores on the Vindictive/Self-Centered subscale-and that BDD severity was modestly correlated with scores on this subscale-is consistent with these prior findings. In a study of 58 adults with BDD, 36% reported physical aggression attributed to their BDD symptoms (Perugi et al, 1997). Clinical observations indicate that hostility/aggression may be fueled by anger about looking "abnormal," an inability to fix the perceived appearance defects, feeling rejected because of one's appearance "defects," and delusions of reference (e.g., believing that others are talking about them because of their appearance) (Phillips, Siniscalchi, et al, 2004).…”
Section: Discussionmentioning
confidence: 98%
“…Quantitative studies have demonstrated that the condition leads to impaired functioning in relationships, socializing, and intimacy as well as to a decreased ability to function at work, in school, or in other daily activities (Perugi et al 1997;Phillips 2009). BDD is associated with significant distress, shame, disability, and suicidality (Crerand et al 2005;Fang and Wilhelm 2015;Phillips 1991;2007;Phillips and Menard 2006).…”
Section: Body Dysmorphic Disorder (Bdd) Is a Psychiatric Disorder Defmentioning
confidence: 99%